A Digital System Model for Healthcare Management in Thai Supply Chain - Artaphon Chansamut (ExcelingTech, 2023)
The paper is a survey study. The paper title is a digital system model for healthcare management in Thai supply chain. The paper finding has been found that a digital system model for healthcare management in Thai supply chain comprises six main elements, namely, manufacturer, Purchasers, Healthcare provider, customer and satisfaction. All elements are connected with digital. A sample group are ten experts. The research tool was evaluation form to evaluate a digital system model for healthcare management in Thai supply chain. The data is analysed by arithmetic means and standardized deviations. The evaluation results a digital system model for healthcare management in Thai supply chain from ten experts was appropriate in a good level which mean that a digital system model for healthcare management in Thai supply chain can be appropriately applied in actual work settings.